Ergonomics Implementation in Manufacturing Industries: Management Commitment for Financial Benefits - Maldonado-Macías, Aide Aracely (Springer, 2021)
Ergonomics is a multidisciplinary science that seeks to adapt systems and products to human capacities and limitations. Therefore, Ergonomics leads to benefits in terms of health, quality of life, and safety, as well as to financial benefits. However, its implementation process is slow and complex as it takes effective analysis to determine critical factors for a successful implementation and the attainment of such benefits. This chapter offers an analysis by structural equations modeling to identify those critical success factors as well as the way they relate to financial benefits. Four stages in the implementation process were considered and a 114-item questionnaire was developed and validated for data collection within manufacturing companies. The questionnaire was administered to a sample of 139 individuals in middle and upper management positions, showing direct, indirect and total effects of Ergonomics implementation and the role of management commitment standing out as a critical factor to obtain financial benefits.